Technocorporal poetics: Runway No. 13 as scenic ritual (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article analyzes how Alexander McQueen’s No.13 show marked a turning point in fashion by integrating technology as a narrative and emotional element. In the context of the turn of the millennium, McQueen reconfigures the runway as a performative space where body, machine, and fashion converge. Through the robotic arms scene, he introduces a technocorporal poetics that anticipates a new aesthetic in which the digital inhabits the stage beyond screens.
Keywords: Fashion show; performance; robots; Alexander McQueen; digital scenography